Green Reuse : A Gamified Recycle Management System - Panita, Prepan (2023)
The Green Reuse Gamified Recycle Management System aims to improve the old method recycling system into a better and more efficient one. The traditional recycling method is inconvenient for customers because it necessitates manual labor and can lead to mistakes due to a lack of expertise in waste separation. They tend to store or dispose of waste. Improper waste disposal can pollute the environment, harming human health. Most electronic waste contains toxic lead, mercury, and lithium. As a result, this application has been developed for the FKOM Community in order to assist users in the correct separation of waste material and to motivate users to bring their recyclables or waste to a recycling center. Users can also get points for recycling, which they can then use to get a voucher. With this method, the user is more actively involved in waste disposal.